Visualisation of reactive oxygen species during stress of spearmint (Mentha spicata L.) - Chananchida Janpen (2019)
© 2019, IndianJournals.com. All rights reserved. The present study is the first to describe the detection of Reactive Oxygen Species (ROS) in spearmint (Mentha spicata L.) grown under nutrient stress conditions through 3,30-diaminobenzidine (DAB) and nitro blue tetrazolium chloride (NBT) histochemical methods. Spearmint cuttings grown under manganese and salt conditions showed toxicity and stunted growth after 10 and 20 days of the stress treatments (> 2.5 mM for the manganese and >100 mM for the saline stress). These abiotic stresses induced the production of ROS in the leaf tissue of the spearmint. Accumulation of hydrogen peroxide was characterised as brown spots by DAB polymerisation which was noticed on leaf tissues from the plants grown under 2.5 and 5 mM concentrations of manganese as well as 300 mM concentration of salt. Furthermore, accumulation of superoxide anion was also characterised as blue pigments based upon the ability of cells to reduce NBT. Level of the secondary metabolite menthol was also significantly increased in response to the ROS production. Our study confirmed the validity of use of DAB and NBT stains in elucidating ROS accumulation in cells of spearmint, the important medical plant under nutrient stress conditions.